Hydrogen Sulfide (H2S)-Releasing Compounds: Therapeutic Potential in Cardiovascular Diseases - Zhang, Lei; Wang, Yanan; Li, Yi; Li, Lingli; Xu, Suowen; Feng, Xiaojun; Liu, Sheng (Frontiers in Pharmacology, 2018)
Cardiovascular disease is the main cause of death worldwide, but its pathogenesis is not yet clear. Hydrogen sulfide (H2S) is considered to be the third most important endogenous gasotransmitter in the organism after carbon monoxide and nitric oxide. It can be synthesized in mammalian tissues and can freely cross the cell membrane and exert many biological effects in various systems including cardiovascular system. More and more recent studies have supported the protective effects of endogenous H2S and exogenous H2S-releasing compounds (such as NaHS, Na2S, and GYY4137) in cardiovascular diseases, such as cardiac hypertrophy, heart failure, ischemia/reperfusion injury, and atherosclerosis. Here, we provided an up-to-date overview of the mechanistic actions of H2S as well as the therapeutic potential of various classes of H2S donors in treating cardiovascular diseases.